SERUM URIC ACID, TRIGLYCERIDES, TOTAL CHOLESTEROL AND HDL-C MEASUREMENTS IN PRE-ECLAMPTIC WOMEN - BISWAJIT DAS; SHASHI KANT VERMA; SUMERU SAMANTA; AYAZ K. MALLICK (International Journal of Pharma and Bio Sciences, 2013)
The present study has been undertaken to compare the maternal serum values of uric acid, triglycerides, total cholesterol and HDL-C between pre-eclamptic women and normotensive pregnant women. Study includes 80 women divided into two groups. Estimation of serum uric acid, triglycerides, total-cholesterol and HDL-C were analyzed by Modified Trinder Peroxidase, CHOD-PAP and Phosphotungstic acid precipitation method, using Erba Chem-5 plus semi-autoanalyser. Our results shows the mean maternal age and gestational age of group-I were statistically significant (p<0.05) than group-II. The systolic, diastolic blood pressure of group-I women were significantly higher than group-II women. Mean serum uric acid and triglycerides levels were significantly increased in group-I in comparison to group-II,p<0.05. There was no difference in the mean values of total-cholesterol between cases (group-I) and control (group-II), p>0.05; but the mean levels of HDL-C were significantly higher in group-II in compared to group-I, p<0.05. Women having pre-eclampsia had elevated levels of serum uric acid and altered triglycerides, total cholesterol and HDL-C values in maternal serum. These levels may have cause and effect relationship with these disorders.